Identification of a unique three‐component sex pheromone produced by the tea black tussock moth, Dasychira baibarana (Lepidoptera: Erebidae: Lymantriinae). Issue 6 (20th April 2022) - Magsi, Fida Hussain; Li, Zhaoqun; Cai, Xiaoming; Yamamoto, Masanobu; Bian, Lei; Zhao, Yingjie; Zhou, Li; Xiu, Chunli; Fu, Nanxia; Ando, Tetsu; Luo, Zongxiu; Chen, Zongmao
Abstract: BACKGROUND: The tea black tussock moth Dasychira baibarana Matsumura is a devastating pest in tea plantations that causes substantial economic losses. Presently, there is no effective method to control this pest other than pesticide application. The identified sex pheromone of D. baibarana could be used for detecting and monitoring this pest. RESULTS: Gas chromatography–electroantennogram detection showed that D. baibarana male moth antennae responded strongly to three components in the female sex pheromone gland, which were identified as: (3 Z, 6 Z )‐ cis ‐9, 10‐epoxyhenicosa‐3, 6‐diene (Z3, Z6, epo9‐21:H) (I ), (3 Z, 6 Z, 11 E )‐ cis ‐9, 10‐epoxyhenicosa‐3, 6, 11‐triene (Z3, Z6, epo9, E11‐21:H) (II ) and (3 Z, 6 Z )‐henicosa‐3, 6‐dien‐11‐one (Z3, Z6‐21:11‐one) (III ). Dasychira baibarana uses a unique composition of an epoxydiene, epoxytriene, and dienone with the same 3, 6‐dienyl motif as its sex pheromone. The epoxytriene and dienone were not previously characterized as insect pheromone components. Electroantennogram analysis showed that each synthetic compound strongly stimulated male antennae, and compounds II and III elicited stronger responses than compound I . A wind tunnel bioassay and field trapping experiments proved that, ternary blends of compounds I –III attracted D. baibarana . Efficient attraction was achieved with a rubber septum baited with 500 μg of a mixture of compounds I –III at the ratio 25:20:55. CONCLUSION: The three identified compounds elicited an electroantennogram response in D. baibarana male moth antennae, and a mixture of the three components at the ratio 25:20:55 attracted D. baibarana male moths in a wind tunnel assay and field trapping experiments. This blend could be used for integrated management of D. baibarana in tea plantations. © 2022 Society of Chemical Industry. Abstract : Application of chemical cues produced by females to attract con‐specifics is used as a sustainable control method. Dasychira baibarana produces a blend of unique structural sex pheromone compounds. The blend of compounds have been identified which has led to the foundation of a systematic approach to suppress the pest in tea plantations.